PENGARUH WORK-LIFE BALANCE TERHADAP EMPLOYEE ENGAGEMENT PADA PEGAWAI BIRO SUMBER DAYA MANUSIA KEMENTERIAN KEUANGAN RI - Chaniago, Putri Auriel; Rahmawati, Siti (Journal of Management Small and Medium Enterprises (SMEs), 2024)
The level of competitiveness of Indonesian human resources (HR) in the world is recorded to have risen four ranks to position 47 based on the results of the Institute for Management Development World Talent Ranking (IMD WTR) 2023 research. The Indonesian Ministry of Finance realizes that one of the greatest strengths in an organization to achieve this lies in its human resources (HR). This study aims to identify the perceptions of employees of the Ministry of Finance's HR Bureau regarding work-life balance and employee engagement and to analyze the influence of work-life balance dimensions on employee engagement. The methods used are descriptive analysis and multiple linear regression analysis with SPSS 26. The results of the study show that employee perceptions of work-life balance and employee engagement are classified as good criteria, then the work-life balance has an effect on employee engagement, then there are two variables, namely Work Interference Personal Life and Personal Life Interference Work have an effect on employee engagement. The variables Work Enhancement of Personal Life and Personal Life Enhancement of Work have no effect on employee engagement. It can be concluded that employees can distinguish and understand their roles and responsibilities both in work and in their personal lives when working. Keywords: Employee engagement; Ministry of Finance; Work-life balance